Comparison of the efficacy of dienogest and GnRH-a after endometriosis surgery - Mingjun Tang; Wenhui Yang; Haiyan Zhang (BMC, 2023)
Abstract Objective To compare the efficacy of dienogest and GnRH-a after endometriosis surgery. Methods Patients with endometriosis who were admitted to our hospital from December 2020 to March 2022 were randomly collected. A total of 81 patients were collected and divided into 40 cases in the control group and 41 cases in the observation group. Among them, the control group was treated with GnRH-a drug, and the observation group was treated with dienogest (DNG). Results The study found that the therapeutic effects of the two drugs were basically the same in patients with endometriosis. The VAS and Kupperman scores of the control group were 0.78 ± 0.8, 3.9 ± 1.84, P < 0.05, respectively; the VAS and Kupperman scores of the observation group were 0.73 ± 0.78, 1.55, respectively ± 1.24, P < 0.05, the difference was statistically significant.In the case of postoperative recurrence, the observation group was better than the control group, with 8 cases of recurrence in the control group and 2 cases of recurrence in the observation group, P < 0.05. Conclusion In the comparison of postoperative efficacy of the two drugs on patients with endometriosis, dienogest is better than GnRH-a adjuvant drug in postoperative recurrence, and has a good improvement and application, which is worthy of further promotion in clinical practice.